PERAN PRAMUSAJI DALAM MENANGANI GUEST COMPLAINTS DI RESTORAN SANGKAR LOBSTER HOTEL LOCCAL COLLECTION - Maria Beatrix Rahinart Wellalangi (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2022)
The aims of this research are 1) to find out the types of complaints that occur at Sangkar Lobster Restaurant, Loccal Collection Hotel and 2) to find out the role of a waitress in handling guest complaints at Sangkar Lobster Restaurant, Loccal Collection Hotel. The research design of this study is descriptive qualitative method. The data are obtained by three techniques of data collections. Those are interview, observation, and direct documentation. The result of the research shows that there are three types of guest complaints including service-related complaints, mechanical complaints, and attitudinal complaints. The handling of guest complaints by waiters at the Sangkar Lobster Restaurant, Loccal Collection Hotel is carried out using the HEAT method. This method stands for Hear, Empathize, Apologize, and Take proper action. Keywords: Waiter, Guest Complaints